Pengaruh Struktur Modal, Ukuran Perusahaan, Efektifitas Aset, dan Efisiensi Operasional Terhadap Financial Performance Pada Perusahaan Food and Beverages yang Terdaftar di BEI Tahun 2018 – 2022 - Sentany, Cecilia; Ariesa, Yeni; Chandra, Joseph Paul (JEBIM Prima, 2023)
This study tries to investigate how capital affects financial performance. Effectiveness of assets, firm size, and organizational structure. The study's data source was the annual financial reports of the food and beverage companies that were traded on the Indonesia Stock Exchange (BEI) between 2018 and 2022. There are a total of 26 companies in the example strategy. The original analytical strategy included both statistical testing with panel data regression techniques and hypothesis testing with F and T tests, followed by traditional assumption tests. The study's findings indicate that the Indonesia Stock Exchange (BEI) would significantly impact the financial performance of the food and beverage sector from 2018 to 2022 if structural, organizational, and operational efficiency are all enhanced. Partially, financial performance is completely unaffected by the DER variable. Even if it isn't particularly significant, the SIZE variable is linked to financial performance. The TATO variable is pertinent to Financial Performance but not very significant. Financial performance is negatively impacted by the CRR variable, although not significantly. The study's coefficient of determination is 0.429382; this means that while other factors may account for the remaining 58% of the variance in Financial Performance, the independent variables DER, SIZE, TATO, and CRR may explain 42% of it.